Ta’arud Hadis Tentang Ziarah Kubur Dalam Perspektif Empat Mazhab - Nurhadi, Nurhadi (Religia: Jurnal Ilmu-Ilmu KeIslaman, 2019)
This article discusses the grave pilgrimage, visits someone's grave with the intention of praying for it and takes lessons from death called the pilgrimage of the grave. The problem in this paper is that there is a contradictory hadith about grave pilgrimage. In the early days of the arrival of Islam, the pilgrimage of the tomb was forbidden from the Shari'ah of Islam (forbidden by the Prophet) because the friends at that time were still obsessed with the culture of kejahiliyahan, which made the grave a place of cult and the weak faith of Muslims. After the spirit of Islam is strong in the soul and heart of the heart, the Messenger of Allah recommends it. Even the portion of the sunnah of the Prophet and wasilah to get his syafa'at is to visit his grave. So in the philosophy of Islamic law, the tomb pilgrimage has a purpose including several benefits for pilgrims, for example taking ibrah (lessons), can soften the heart, remind death and realize the existence of the Hereafter (doomsday). While the benefits for the inhabitants of the tomb (the mayyit), namely with the presence of prayers and greetings that were read and pronounced from the pilgrims, then it became a relief to alleviate the torment of his grave, as in the hadith of the Prophet. The circumcision of the law is the grave pilgrimage in a review of the philosophy of Islamic law, provided that the grave pilgrimage gives greetings and prayers to the grave expert, does not sit and step on the grave, not slaughter the animals on it, not bernadzar to those who have died. The tomb pilgrimage does not include bid'ah, even the sunnah because the Messenger of Allah made a tomb pilgrimage at the tomb of his mother Aminah. The hadiths about the prohibition of grave pilgrimage must be compromised with the recommendations of the tomb pilgrimage. So that at the meeting point according to the philosophy of Islamic law, the pilgrimage of the grave category of practice recommended and circumcised, is not part of the practice that is prohibited or dibid'ahkan (bid'ah astray)